Sukuk Ijarah sebagai Instrumen Pembiayaan Syariah: Peluang, Tantangan, dan Kepatuhan Syariah - Rachmawati, Dwi (Qawanin: Jurnal of Economic Syaria Law, 2025)
Sukuk ijarah is one of the Islamic financial instruments based on lease contracts (ijarah) on the benefits of assets. This instrument serves as a significant alternative source of financing in supporting infrastructure development and national economic growth, particularly in Indonesia, which has the largest Muslim population in the world. This study aims to examine the opportunities offered by sukuk ijarah as a sharia compliant financing instrument, identify the challenges in its implementation in Indonesia, and analyze how sharia compliance principles are applied in the issuance of sukuk ijarah. This research employs a qualitative approach using the library research method. The analysis is conducted descriptively and analytically by examining academic and regulatory substance related to these issues. The findings indicate that sukuk ijarah has promising prospects as a sharia investment instrument due to its fixed returns, asset-backed structure, and relatively stable design. To optimize its role, regulatory strengthening, enhanced inter-institutional synergy, and consistent public education are required to ensure the sustainability and integrity of the national Islamic financial market. Sukuk ijarah merupakan salah satu instrumen keuangan syariah yang berbasis akad sewa atas manfaat aset. Instrumen ini menjadi alternatif pembiayaan yang signifikan dalam mendukung pembangunan infrastruktur dan perekonomian nasional, khususnya di Indonesia sebagai negara dengan populasi Muslim terbesar di dunia. Penelitian ini bertujuan untuk mengkaji peluang yang ditawarkan oleh sukuk ijarah sebagai instrumen pembiayaan syariah, mengidentifikasi tantangan dalam penerapannya di Indonesia, serta menganalisis bagaimana prinsip kepatuhan syariah diterapkan dalam penerbitan sukuk ijarah. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi pustaka. Analisis dilakukan secara deskriptif-analitis dengan menelaah substansi akademik dan regulatif terkait isu-isu tersebut. Hasil penelitian menunjukkan bahwa sukuk ijarah memiliki prospek menjanjikan sebagai instrumen investasi syariah karena menawarkan imbal hasil tetap, berbasis aset nyata, dan memiliki struktur yang relatif stabil. Untuk mengoptimalkan perannya, diperlukan penguatan regulasi, peningkatan sinergi antar lembaga, serta edukasi publik yang konsisten untuk menjamin keberlanjutan dan integritas pasar keuangan syariah nasional.